Composite metal foil and preparation method and application thereof
By using a porous polymer base film in the composite fluid collection and embedded metal, the problem of insufficient bonding force between the polymer base film layer and the metal layer is solved, and the peel strength of the composite metal foil and the safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411991957.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the existing composite fluid collecting technology, the bonding force between the polymer base film layer and the metal layer is insufficient, resulting in the copper foil being easily peeled off and shedding, and the bonding force is poor.
A porous polymer base film is used as the base film, and during the metal plating process, part of the metal is allowed to enter the pores of the porous polymer, thereby forming a porous polymer base film with metal embedded in it, and improving the bonding strength between the metal layer and the base layer.
By embedded metal porous polymer base film, the peel strength of the composite metal foil is significantly improved, the mechanical strength and thermal shrinkage performance of the base film are improved, and the safety performance of the battery is enhanced.
Smart Images

Figure CN119786620A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite metal foils, and in particular relates to a composite metal foil and a preparation method and application thereof. Background Art
[0002] Conventional lithium-ion batteries (LIBs) are constantly evolving to improve their electrochemical performance and safety. In the past decade, research on electrode and electrolyte materials has significantly promoted the development of conventional batteries. However, the current collector in conventional LIBs has not received enough attention. As an important unit that collects and disperses electrons from electrodes and conducts current, the performance of the current collector significantly affects the performance of LIBs. The current collector has the necessary properties such as electrochemical stability, conductivity, mechanical strength, density, sustainability, and cost.
[0003] The wettability and surface properties of the current collector affect the electrochemical performance of LIBs, the surface cleanliness and cutting quality affect the safety of LIBs, and the thickness seriously affects the energy density of LIBs. Reducing the thickness of the current collector helps to increase the mass ratio and volume energy density of the battery. Therefore, with the development of LIBs, the thickness of copper foil has been reduced to 4-8μm, and the mass ratio in the battery has dropped from 19.3% to about 6%, respectively. Although the thickness of the current collector can be further reduced, the ultra-thin current collector with weak mechanical properties is prone to wrinkles and fractures during the coating process. In addition, the manufacturing cost will continue to increase.
[0004] To meet the growing demand for high energy and safety in batteries, especially for the commercialization of electric vehicles, further advances are needed. Metallized plastic current collectors (MPCCs) with metal-polymer-metal multilayer composite structures are an innovative solution. This approach has several advantages. First, it effectively reduces the weight and thickness of lithium-ion batteries, thereby increasing their energy density. Second, the polymers with electrical insulation and high elongation properties in MPCCs significantly improve the safety performance of lithium-ion batteries by preventing thermal runaway.
[0005] At present, there have been reports of new current collector structures in which a metal layer is carried on a polymer base film layer, the metal layer is used to carry an electrode active material layer, and the metal layer is located on at least one surface. The main disadvantages of existing composite current collector technology are: copper foil is easy to peel off, fall off, and has poor bonding strength. The main reasons for this disadvantage are the differences in chemical structure, physical properties, and improper surface treatment between the polymer base film layer and the metal layer.
[0006] In the prior art, this defect is usually compensated by adding a binder or multiple conductive layers, but this will increase the number of processes. How to more effectively and conveniently improve the bonding force between the composite current collector polymer base film layer and the metal layer is a problem worth studying in this field. Summary of the invention
[0007] The purpose of the present invention is to solve the insufficient bonding strength between a polymer-based film layer and a metal layer in the prior art and to provide a composite metal foil having higher peeling strength.
[0008] Another object of the present invention is to provide a method for preparing the composite metal foil.
[0009] Another object of the present invention is to provide applications of the composite metal foil.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] A composite metal foil comprises a substrate layer and a metal layer on the surface of the substrate layer, wherein the substrate layer comprises a porous polymer substrate film and metal embedded in the pores of the porous polymer substrate film; the content of the metal in the substrate layer is 8-25wt%.
[0012] The metal in the base layer and the metal layer covering the surface of the base layer are formed in the same process.
[0013] In the prior art, especially in the field of batteries, the base film for preparing composite metal foil generally uses a polymer base film without holes. However, the inventors found that when using a porous polymer as a base film, part of the metal will enter the pores of the porous polymer during the metal plating process, thereby forming a porous polymer base film embedded with metal. This base film is more firmly combined with the metal layer, which can make the composite metal foil have a higher peel strength.
[0014] Preferably, the porosity of the porous polymer base film is 15-40%. Appropriate porosity can make the composite metal foil have good mechanical strength and thermal shrinkage performance. More preferably, the porosity of the porous polymer base film is 20-35%.
[0015] The method for preparing the porous polymer-based membrane in the present invention can be prepared by referring to the known technology for preparing porous polymer-based membranes. For example, when the polymer is polyolefin, it can be prepared by referring to the method described in CN118772479A.
[0016] Preferably, the polymer of the porous polymer base membrane is selected from polyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyimide, polyethylene terephthalate, polypropylene, polysulfone, polydimethylsiloxane, polyamide, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyamide urea, polyformaldehyde, epoxy resin, phenolic resin, silicone rubber, polycarbonate, polyvinyl alcohol, polyethylene glycol or any combination thereof.
[0017] Preferably, in the matrix layer, the mass volume of the metal in the matrix layer is 0.04-0.12 g / cm 3 .
[0018] More preferably, in the matrix layer, the mass volume of the metal in the matrix layer is 0.055 to 0.09 g / cm 3 In the present invention, the mass of the metal in the base layer can be obtained by subtracting the mass of the metal layer from the mass of the composite metal foil, and then subtracting the mass of the porous polymer base film. The mass of the metal layer can be obtained by a physical method or a calculation method in conjunction with a scanning electron microscope. The physical method is to peel off the metal layer with tape and then weigh it.
[0019] The calculation method is to determine the thickness of the metal layer by scanning electron microscopy, and obtain the thickness according to metal layer thickness×metal layer area×metal density.
[0020] Preferably, the peel strength of the composite metal foil is greater than 400 N / m.
[0021] More preferably, the peel strength of the composite metal foil is greater than 500 N / m.
[0022] In the present invention, the peel strength of the composite metal foil is tested as follows:
[0023] The prepared flat metal foil sample is cut into a specimen with a width of 24 mm and a length of 300 mm, and one end of the cut specimen is folded with the adhesive surface to form a folded layer of about 12 mm long; the other end of the specimen is pasted to one end of the steel plate and rolled twice with an adhesive tape roller at a speed of 600 mm / min, and then placed in an electronic peeling tester with the test speed set to 250 mm / min; the equipment automatically records the force value during the peeling process and reports the peeling strength of the specimen accordingly.
[0024] Preferably, the thickness of the base layer is 2-8 μm.
[0025] Preferably, the thickness of the metal layer is 0.1-1.0 μm.
[0026] Preferably, the metal layer is formed by chemical plating.
[0027] The preparation method of the composite metal foil comprises the following steps:
[0028] S1 performs roughening treatment on the porous polymer base membrane;
[0029] S2 performs sensitization treatment on the roughened base film;
[0030] S3 performs water washing on the base film after the sensitization treatment;
[0031] S4 activates the base film after the water washing treatment;
[0032] S5 performs chemical plating on the activated base film to cover the surface of the base layer with a metal layer.
[0033] More preferably, the roughening treatment in S1 is achieved by plasma treatment.
[0034] The plasma treatment may be performed once or multiple times.
[0035] More preferably, the power of each plasma treatment is 50 to 150 W. The duration of each plasma treatment is 30 to 180 seconds.
[0036] More preferably, the sensitization treatment in S2 is to immerse the roughened base film in a stannous salt solution, and the immersion time is preferably 1 to 2 minutes.
[0037] The stannous salt solution is preferably a stannous chloride solution, and its concentration is preferably 30-40 g / L.
[0038] The purpose of the water washing treatment in S3 is to form a gel film on the base film after the sensitization treatment, so as to facilitate the activation treatment in S4. The water washing treatment can be specifically washing the sensitized base film in deionized water at a temperature of 20-50°C.
[0039] Preferably, the washing time may be 10 to 20 seconds.
[0040] The purpose of S4 activation treatment is to prepare for chemical copper plating.
[0041] More specifically, the activation is achieved by immersing the washed base film in an activation liquid.
[0042] The immersion time is 1 to 2 minutes. The activation liquid can be a palladium chloride solution, and its concentration can be 0.5-1.0 g / L.
[0043] The chemical metal plating in S5 can be performed by referring to the existing method of plating metal on the surface of the base film.
[0044] More specifically, taking copper plating as an example, the main components of the chemical metal plating copper plating solution include 10.0 g / L copper sulfate, 15.0 g / L sodium hydroxide, 36.0 g / L potassium sodium tartrate tetrahydrate, 10.0 g / L disodium ethylenediaminetetraacetic acid, 10.0 mL / L formaldehyde, 5.0 ml / L 2'2-bipyridine, and 5.0 g / L nickel sulfate mixed solution.
[0045] The time for the chemical copper plating is 3 to 5 minutes.
[0046] Preferably, before S1, a step of cleaning the base film is also included. The purpose of cleaning is to remove oil stains or impurities on the base film.
[0047] Preferably, after S5 is completed, a step of performing an antioxidant treatment is further included.
[0048] More preferably, in the present invention, the metal layer is a metal layer formed of copper, nickel and / or aluminum or a carbide layer of copper, nickel and / or aluminum. More preferably, the metal layer is a metal layer formed of copper.
[0049] The composite metal foil is used as a negative electrode current collector.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The present invention provides a composite metal foil, which has a suitable amount of metal embedded in a base layer, is more tightly combined with a metal layer located on the surface of the base layer, and the metal also supplements the strength of the base film and improves the bending resistance of the base film, so that the composite metal foil has better peeling strength. The composite metal foil, especially the copper foil, can be used as a negative electrode current collector to achieve lightweight battery products, not only improve the peeling strength of the copper foil, but also improve the conductivity of the copper foil in a local area; at the same time, the copper metal embedded structure also provides a fast thermal response interface to improve the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a SEM schematic diagram of the composite metal foil prepared in Example 4.
[0053] Figure 2 This is an enlarged SEM schematic diagram of the composite metal foil embedded layer structure prepared in Example 5.
[0054] Figure 3 This is a SEM schematic diagram of the composite metal foil prepared in Comparative Example 3;
[0055] Among them, 1 is the metal layer, 2 is the substrate layer, 3 is the metal embedded in the pores of the substrate layer, and 4 is the pores of the substrate layer. DETAILED DESCRIPTION
[0056] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0057] Examples 1 to 5 and Comparative Examples 1 and 2
[0058] Referring to Table 1, PE-based films (porosity) with different porosities were selected, and composite copper foils were prepared according to the following process.
[0059] The PE base film was homemade, and was prepared by adjusting parameters with reference to the method described in the example of CN118772479A.
[0060] Basement membrane porosity P = [1-(basement membrane mass / skeleton density) / basement membrane apparent volume] × 100%
[0061] Base film quality: The actual quality of the PE base film can be measured by a balance.
[0062] Skeleton density: the density of the raw materials used for PE-based membranes, that is, the density of the raw materials when a porous structure is not produced.
[0063] Apparent volume of base film: The volume of PE base film in its natural state (porous structure has been made), which can be obtained by physical measurement.
[0064] Composite copper foil preparation:
[0065] S1 base film roughening treatment is plasma treatment:
[0066] Place the decontaminated base film into the vacuum plasma chamber, close the valve, turn on the power, and evacuate to 5×10 -2 Pa, introduce working gas, which is one of nitrogen, argon, oxygen or a mixed gas, the working gas pressure is controlled at 1Pa, the working power is set between 150W, the temperature is 25℃, the time is 90 seconds, and a roughened base film after plasma treatment is obtained.
[0067] Sensitization of S2 basement membrane:
[0068] The roughened base film is completely immersed in the sensitizing liquid for 1-2 minutes at a temperature of 30°C.
[0069] The sensitizing solvent is a homemade stannous chloride solution with a concentration of 30 g / L.
[0070] Washing treatment of S3 base film:
[0071] The sensitized basement membrane is taken out from the sensitizing liquid, and washed in deionized water at a temperature of 45° C. to form a gel film on the surface of the basement membrane. The washing time is 10-15 seconds.
[0072] Activation of S4 basement membrane:
[0073] The cleaned base film is completely immersed in the activation liquid for 1-2 minutes at a temperature of 25°C.
[0074] The activation solvent is a self-made palladium chloride solution with a concentration of 1.0 g / L.
[0075] S5 chemical copper plating:
[0076] Chemical copper plating is performed on the surface of the base film after S4 treatment.
[0077] The chemical copper plating solution is composed of 10.0g / L copper sulfate, 15.0g / L sodium hydroxide, 36.0g / L potassium sodium tartrate tetrahydrate, 10.0g / L disodium ethylenediaminetetraacetate, 10.0mL / L formaldehyde, 5.0ml / L 2'2 bipyridine, and 5.0g / L nickel sulfate mixed solution. After the above solution components are configured, mix and stir them evenly. Put the treated base film horizontally into the chemical copper plating solution, the chemical plating time is 3 to 5min, the temperature is 40°C, and ultrasonic vibration is used to make the solution more uniform. After the copper plating is completed, take it out, wash it with deionized water and do antioxidant treatment, and finally put it into a drying oven to dry.
[0078] Comparative Examples 3 and 4
[0079] PE-based films with porosity of 0% and 30% were respectively treated by magnetron sputtering, and then chemical copper plating was performed under the same conditions as in S5 to obtain composite copper films as Comparative Examples 3 and 4. Specific operation of magnetron sputtering:
[0080] The front door of the vacuum chamber was closed, and then the chamber was evacuated to 8.0×10 -4 Pa. Introduce argon gas of different flow rates and adjust the gate valve position to adjust the working pressure to the required range. When the working pressure is stable, set the coating roller speed to 10m / min, set the required RF sputtering power at 350W, set the working pressure within the range of 0.02Pa, and start to deposit the film. The film deposition time is 5mins.
[0081] The test method for peel strength is:
[0082] The prepared flat metal foil sample is cut into a specimen with a width of 24 mm and a length of 300 mm, and one end of the cut specimen is folded with the adhesive surface to form a folded layer of about 12 mm long; the other end of the specimen is pasted to one end of the steel plate and rolled twice with an adhesive tape roller at a speed of 600 mm / min, and then placed in an electronic peeling tester with the test speed set to 250 mm / min; the equipment automatically records the force value during the peeling process and reports the peeling strength of the specimen accordingly.
[0083] Copper content in the base layer = mass of copper in the base layer (g) / mass of base film (g)
[0084] The mass of copper in the base layer = the mass of the composite copper foil (g) - the mass of the base film (g) - the mass of the copper layer (g);
[0085] In addition, it was observed whether copper was embedded in the base layer by scanning electron microscopy and EDS on the cross section.
[0086] The mass of the copper layer can be obtained by a physical method or by a calculation method in combination with a scanning electron microscope. The physical method is to peel off the copper layer with an adhesive tape and then weigh it.
[0087] The calculation method is to determine the copper layer thickness by scanning electron microscopy, and obtain the copper layer mass according to the copper layer thickness×copper layer area×copper density. In the embodiment, the calculation method is used to obtain the copper layer mass.
[0088] The mass volume content of copper particles in the base layer = the mass of the base film copper (g) / the apparent volume of the base film copper (cm 3 )
[0089] Bending resistance test: Use cutting equipment to prepare different samples of the same size of 15mm×100mm. Use a bending resistance tester or bend them manually for dozens of times to observe the peeling of the copper foil surface and the falling of copper powder. Use an optical microscope to observe the surface wrinkles and cracks at the bending point for comprehensive judgment.
[0090] The quality is judged as excellent if the copper foil is not peeled off, no copper powder falls off, and there are tiny cracks on the surface; it is judged as relatively good if the copper foil is not peeled off, a small amount of copper powder falls off, and there are small cracks on the surface; it is judged as fair if the copper foil is not peeled off, a small amount of copper powder falls off, and there are cracks on the surface.
[0091] Safety performance test: The composite copper foils of Examples 1 to 5 were prepared into batteries, and in the small-capacity soft-pack battery puncture test, no fire or smoke occurred.
[0092] Table 1 Test data of composite copper foil prepared in Examples 1 to 5 and Comparative Examples 1 to 4
[0093]
[0094]
[0095] From Examples 1 to 5 and Comparative Examples 1 and 3, and Figures 1 to 3 It can be seen that the composite metal foil in which the metal is effectively embedded in the base film layer is prepared by using a porous polymer base film, and the composite metal foil has a higher metal peeling strength. As can be seen from Comparative Example 2, if the porosity of the polymer base film is low, it is difficult to allow a sufficient amount of copper to enter the polymer base film, thereby making it difficult to achieve the desired effect of improving the peeling strength. As can be seen from Comparative Example 4, other processing methods cannot allow copper to enter the polymer base film more effectively, resulting in an insignificant improvement in the peeling strength.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite metal foil, comprising a substrate layer and a metal layer located on the surface of the substrate layer, characterized in that: The base layer comprises a porous polymer base film and metal embedded in the pores of the porous polymer base film; in the base layer, the content of the metal is 8-25wt%.
2. The composite metal foil according to claim 1, characterized in that: The porosity of the porous polymer-based membrane is 15-40%.
3. The composite metal foil according to claim 1 or 2, characterized in that: The porosity of the porous polymer-based membrane is 20-35%.
4. The composite metal foil according to claim 1, characterized in that: The polymer of the porous polymer base membrane is selected from polyethylene, polytetrafluoroethylene, polyvinylidene fluoride, polyimide, polyethylene terephthalate, polypropylene, polysulfone, polydimethylsiloxane, polyamide, polystyrene, polyvinyl chloride, aramid, polyphenylene dicarboxylate, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, polypropylene, polyamide urea, polyoxymethylene, epoxy resin, phenolic resin, silicone rubber, polycarbonate, polyvinyl alcohol, polyethylene glycol or any combination thereof.
5. The composite metal foil according to claim 1, characterized in that: In the matrix layer, the mass volume content of the metal in the matrix layer is 0.04 to 0.12 g / cm 3 .
6. The composite metal foil according to claim 1, characterized in that: The peel strength of the composite metal foil is greater than 400 N / m.
7. The composite metal foil according to claim 1, characterized in that: The thickness of the base layer is 2-8 μm.
8. The composite metal foil according to claim 1, characterized in that: The metal layer is a metal layer formed of copper, nickel and / or aluminum or a carbide layer of copper, nickel and / or aluminum.
9. The method for preparing the composite metal foil according to any one of claims 1 to 7, characterized in that: The steps include: S1. roughening the porous polymer substrate; S2. sensitizing the roughened base film; S3. Washing the sensitized base film; S4. Activating the basement membrane after washing; S5. Perform chemical plating on the activated base film to cover the surface of the base layer with a metal layer.
10. Use of the composite metal foil according to any one of claims 1 to 7 as a negative electrode current collector.
Citation Information
Patent Citations
Fabrication method and application of nickel-fabric current collector
CN108400339A
Flexible conductive film, and preparation method and application thereof
CN111446453A
Current collector and preparation method and application thereof
CN114824283A
Flexible metal-clad plate, electronic device and manufacturing method of flexible metal-clad plate
CN114953640A
Preparation method and preparation device of composite current collector
CN115440985A